Design and validation of a questionnaire for the assessment of tennis players` tactical skills (TST) - Sanchez Mencia, E.; Campos-Rius, J.; Borrajo Mena, E. (Research Quarterly for Exercise and Sport, 2025)
The aim of the present study was to develop and validate a self-assessment questionnaire for tactical skills in tennis. This is the first questionnaire to assess tactical skills in this discipline to our knowledge. The study sample consisted of 253 tennis players at the expert, intermediate, and beginner levels. The age of the tennis players ranged from 18 to 70 years. The results of the content analysis of the questionnaire revealed a three-factor structure, consisting of tactics used in training, tactics used in the match, and decision making in the match, with adequate psychometric properties. Analyses of variance were carried out to compare the results for these three tactical factors with the level of play (expert, intermediate, and beginner) and player profile (complete, serve-volley, offensive, and counter-attacking player). These results showed that expert players scored higher on all three factors. Furthermore, players with a complete profile had statistically higher scores across all three factors compared to serve-volley players. The results and their implications are then discussed.